2021
DOI: 10.1186/s13018-021-02631-y
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0004674 promotes osteosarcoma doxorubicin resistance by regulating the miR-342-3p/FBN1 axis

Abstract: Background The occurrence of chemoresistance is a common problem in tumor treatment. Circular RNA (circRNA) has been confirmed to be related to tumor chemoresistance. However, the role and the underlying molecular mechanism of hsa_circ_0004674 in the chemoresistance of osteosarcoma (OS) are still unclear. Methods The expression of hsa_circ_0004674, miR-342-3p, and fibrillin-1 (FBN1) was determined by qRT-PCR. Cell counting kit 8 assay was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Of these, 43 investigated the molecular regulatory mechanisms of lncRNAs in chemotherapeutic drug resistance in OS, 101 focused on miRNAs, 21 on circRNAs, and one study reported on both lncRNA MEG3 and hsa_circ_0001258 ( Zhu et al, 2019 ). Moreover, 19 overlapping ncRNAs were reported in more than one study, including four lncRNAs (lncRNA SNHG15 [ Sun et al, 2022 ; Zhang et al, 2020a ], lncRNA OIP5-AS1 [ Song et al, 2019 ; Liu and Wang, 2020 ; Sun et al, 2020 ; Kun-Peng et al, 2019 ], lncRNA TUG1 [ Zhou et al, 2020 ; Hu et al, 2019 ], and lncRNA ANRIL [ Li and Zhu, 2019b ; Lee et al, 2021 ]), 13 miRNAs (miR-29b [ Luo et al, 2019 ; Li et al, 2020 ], miR-21 [ Vanas et al, 2016 ; Ziyan and Yang, 2016 ], miR-22 [ Wang et al, 2019c ; Li et al, 2014 ; Meng et al, 2020a ; Meng et al, 2020b ; Zhou et al, 2018b ], miR-199a-3p [ Lei et al, 2018 ; Gao et al, 2015 ], miR-34a-5p [ Pu et al, 2016 ; Pu et al, 2017b ; Pu et al, 2017a ], miR-34a [ Li et al, 2017 ; Novello et al, 2014 ; Chen et al, 2016a ], miR-140-5p [ Wei et al, 2016 ; Meng et al, 2017 ], miR-203 [ Chen et al, 2016a ; Huang et al, 2021 ], miR-19a-3p [ Zhang et al, 2019 ; Wang et al, 2022a ], miR-140 [ Song et al, 2009 ; Zhi et al, 2022 ], miR-29 [ Osaki et al, 2016 ; Xu et al, 2018b ], miR-221 [ Yu et al, 2019 ; Zhao et al, 2013 ], and miR-100 [ Xiao et al, 2017 ; Liu et al, 2016 ]), and two circRNAs (circPTV1 [ Li et al, 2021c ; Kun-Peng et al, 2018a ; Wang et al, 2022c ] and circRNA_0004674 [ Ma et al, 2021 ; Bai et al, 2021 ]) (…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 43 investigated the molecular regulatory mechanisms of lncRNAs in chemotherapeutic drug resistance in OS, 101 focused on miRNAs, 21 on circRNAs, and one study reported on both lncRNA MEG3 and hsa_circ_0001258 ( Zhu et al, 2019 ). Moreover, 19 overlapping ncRNAs were reported in more than one study, including four lncRNAs (lncRNA SNHG15 [ Sun et al, 2022 ; Zhang et al, 2020a ], lncRNA OIP5-AS1 [ Song et al, 2019 ; Liu and Wang, 2020 ; Sun et al, 2020 ; Kun-Peng et al, 2019 ], lncRNA TUG1 [ Zhou et al, 2020 ; Hu et al, 2019 ], and lncRNA ANRIL [ Li and Zhu, 2019b ; Lee et al, 2021 ]), 13 miRNAs (miR-29b [ Luo et al, 2019 ; Li et al, 2020 ], miR-21 [ Vanas et al, 2016 ; Ziyan and Yang, 2016 ], miR-22 [ Wang et al, 2019c ; Li et al, 2014 ; Meng et al, 2020a ; Meng et al, 2020b ; Zhou et al, 2018b ], miR-199a-3p [ Lei et al, 2018 ; Gao et al, 2015 ], miR-34a-5p [ Pu et al, 2016 ; Pu et al, 2017b ; Pu et al, 2017a ], miR-34a [ Li et al, 2017 ; Novello et al, 2014 ; Chen et al, 2016a ], miR-140-5p [ Wei et al, 2016 ; Meng et al, 2017 ], miR-203 [ Chen et al, 2016a ; Huang et al, 2021 ], miR-19a-3p [ Zhang et al, 2019 ; Wang et al, 2022a ], miR-140 [ Song et al, 2009 ; Zhi et al, 2022 ], miR-29 [ Osaki et al, 2016 ; Xu et al, 2018b ], miR-221 [ Yu et al, 2019 ; Zhao et al, 2013 ], and miR-100 [ Xiao et al, 2017 ; Liu et al, 2016 ]), and two circRNAs (circPTV1 [ Li et al, 2021c ; Kun-Peng et al, 2018a ; Wang et al, 2022c ] and circRNA_0004674 [ Ma et al, 2021 ; Bai et al, 2021 ]) (…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, hsa_circ_0000073 promotes malignant behaviors, including proliferation, invasion, and migration, and facilitates MTX resistance of osteosarcoma cells by sponging miR-145-5p and miR-151-3p to upregulate NRAS (105). DOX resistance of osteosarcoma is facilitated by hsa_circ_0004674 through the Wnt/b-catenin pathway via modulation of the miR-342-3p/FBN1 axis (106). Moreover, some circRNAs potentiate DOX resistance and facilitate the progression of osteosarcomas, such as circ_0001721, circSAMD4A, circ_0002060, and circ_0003496 (20,(107)(108)(109).…”
Section: Circrnas and Osteosarcoma Drug Resistancementioning
confidence: 99%
“…DOX resistance of osteosarcoma is facilitated by hsa_circ_0004674 through the Wnt/β-catenin pathway via modulation of the miR-342-3p/FBN1 axis ( 106 ). Moreover, some circRNAs potentiate DOX resistance and facilitate the progression of osteosarcomas, such as circ_0001721, circSAMD4A, circ_0002060, and circ_0003496 ( 20 , 107 109 ).…”
Section: Circrnas and Drug Resistancementioning
confidence: 99%
“…Moreover, new evidence implies that circRNAs may affect acquired chemoresistance [ 87 ]. The above-mentioned mechanisms have been shown to be critical in sarcomagenesis [ 88 , 89 , 90 , 91 , 92 , 93 , 94 ], and a large number of circRNAs have been demonstrated to affect chemoresistance in OS, such as hsa_circ_0004674, hsa_circ_0081001 and circPVT1, among others [ 88 , 95 , 96 , 97 , 98 ].…”
Section: Main Characteristics Of Circrnasmentioning
confidence: 99%
“…According to previous research findings of this group, chemoresistance in OS may be regulated by hsa_circ_0004674-miR-490-3p-ABCC2 and hsa_circ_0004674/miR-1254-EGFR pathways [ 96 , 240 , 241 ]. In addition, Bai et al proposed a new mechanism of hsa_circ_0004674 promoting chemoresistance to DXR by regulating the miR-342-3p/FBN1 axis through the Wnt/β-catenin pathway [ 88 ].…”
Section: Circrnas Functions In Osteosarcomamentioning
confidence: 99%